SELF-CONTROL DAN GRIT MAHASISWA SEMESTER AKHIR DI UNIVERSITAS YUDHARTA PASURUAN - Putri Dewi Kurniawati; Nathania Bayu Astrella (Psikologi Prima, 2023)
Students working on a thesis can experience boredom, lack enthusiasm, and even lack motivation, which can be an obstacle to the completion of the thesis. Researchers distributed grit questionnaires aimed at students working on their theses at Yudharta Pasuruan University and found that most students needed more consistency of interest and higher resilience in trying. Therefore, students who are working on their thesis need to exercise self-control in order to complete it. Self-control is a belief that individuals have in acting and behaving and the ability of individuals to control these behaviors. Students need to have a high level of grit in order to be able to commit to their choices, even though it will be difficult and tedious. This study aimed to determine the effect of self-control on grit in students working on a thesis. The research method used is quantitative, with a sample of 234 8th-semester students working on their thesis. Based on the calculation, the r value is 0.776, which means the correlation between the self-control variable and grit is strong. The r2 value is 0.602, meaning self-control influences 60.2% of student grit. It is known that the sig. The value is 0.000, which is 0.000 <0.05; it can be concluded that there is a significant influence between self-control and grit in students working on their thesis.